(untitled) - Loucks, Daniel P. (New Jersey, 1981)
This book provided information about water resource systems analysts use mathematical models and methods to aid engineers, planners, economists and the public to sort through the myriad of schemes which are and could be proposed,...
Keywords: Water resources development,Phát triển nguồn tài nguyên nước,Water resources development; Mathematical,Kế hoạch,Planning